The effect of exercise motivation on adolescents’ subjective Well-being: chain mediation of physical activity and Social-emotional competency - Kaiyi Zhang; Mingyi Liu; Zikang Yin; Nianxin Kong; Haipei Gong (BMC Public Health)
Abstract Objective Based on the Self-Determination Theory, this study examined the influences on adolescents’ subjective well-being and revealed the chain mediating role of physical activity and socio-emotional competence between exercise motivation and subjective well-being. Methods Motives for Physical Activity Measure (MPAM-R), Subjective Well-Being Scale for Chinese Citizen (SWBS-CC20), Physical Activity Rating Scale (PARS-3), and The Delaware Social-Emotional Competency Scale (DSECS-S) were used to conduct questionnaire surveys on 1,530 junior high school students in Handan, Hebei Province. The data were statistically analyzed by using the SPSS 23.0 and AMOS 23.0 software. Results (1) There is a positive correlation between exercise motivation and subjective well-being, and the direct prediction of subjective well-being is significant; (2) Exercise motivation can indirectly influence adolescents’ subjective well-being through the partial mediation of physical activities and social-emotional competency; (3) Exercise motivation may also indirectly affects adolescents’ subjective well-being through the chain mediation of “physical activities and social-emotional competency”. Conclusion A higher EM may enhance adolescents’ level of PA and SEC, which further contributes to their SWB, which plays an important role in enhancing adolescents’ mental health and maintaining a healthy lifestyle.